Les papyrus de la mer Rouge. - Tallet, Pierre, 1966- (Mémoires publiés par les membres de l'Institut français d'archéologie orientale du Caire ;, 2017)
The Ouadi el-Jarf site, excavated since 2011, is a port on the Red Sea that was used at the beginning of the 4th Dynasty to go by sea to the turquoise and copper mines of the southwestern peninsula of Sinai. In the 2013 campaign, a large batch of papyrus dating from the end of the reign of Cheops was unearthed at the entrance of one of the shop-galleries which are one of the characteristic traits of the site, to this day the most ancient hieratic papyrus ever discovered. They constitute the archives of a team of sailors and are subdivided into two main categories: accounts recording deliveries of different products, and logbooks covering several months of activity of this team. The latter describe missions carried out under the supervision of Inspector Merer and mainly concern the transport by river water of limestone blocks from the quarries of Toura to the construction site of the great pyramid of Cheops, on the other bank of the Nile. This book is the publication of the two best preserved logbooks of this lot.